P229 Hsv management in pregnancy at a joint antenatal-genitourinary clinic in a large maternity hospital in dublin, ireland – a model of care. (8th June 2017) - Lynn, Niamh; Murphy, Sinead; Cunningham, Orla; Lynam, Almida; Lyons, Fiona; Mulcahy, Fiona
Abstract : Introduction: The ultimate goal of HSV management in pregnancy is to prevent perinatal transmission and, where possible, to facilitate vaginal delivery. Methods: Data was collected from antenatal charts of 107 women who reported a history of HSV or who had a documented outbreak during that pregnancy. Descriptive column statistics were used in excel for data analysis. Results: From May 2013 to Feb 2017, 107 Women were seen in the clinic for management of HSV in 108 pregnancies. Median gestation at referral (82/108) was 23/40 (range 2–39/40). Mean age 33yr (range 18–45). 91 (85%) European. 9(8%) HIV+. 82 (76%) reported prior history. 96 (89%) had type-specific serology sent of which 89 (92%) HSV IgG +ve. 28 (31%) HSV 1 & 2 positive, 47 (52%) Type I positive only, 12 (13%) Type 2 positive only, 2 were weak + and not typed. 69 (63%) had STI testing, 100% negative. 4 of the 107 (80%) had primary HSV in that pregnancy. 67 received HSV prophylaxis; 66 valaciclovir; 1 aciclovir. Mean gestation starting prophylaxis was 36/40 (range 20 – 39). Data on mode of delivery on 82 of 107 (76%) pregnancies; 59 (71%) vaginal, 24 (29%) lower segment caesarean sections, none for HSV. Median gestation at delivery of 84 pregnancies 39/40 (range 29 – 41). To date no cases of perinatal HSV transmission have been reported. Discussion: There is good compliance with Irish guidelines on HSV management in pregnancy. HSV2 remains an issue. This combined clinic facilitates good compliance with standard guidelines for HSV management in pregnancy. This model of care should be available across all antenatal settings.